Bangladesh : Policy Options for Crop and Livestock and Aquaculture Insurance - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture is a key sector in Bangladesh, but it is highly exposed to risks. While agriculture is a source of employment and livelihood for nearly one in two adults in Bangladesh and contributes about 16 percent to GDP, it is highly exposed to natural hazards. Indeed, Bangladesh is commonly ranked as one of the most vulnerable countries in the world to natural disasters with agriculture heavily exposed to floods, cyclones, and drought. In 2007, for instance, Cyclone Sidr destroyed 0.69 million hectares of cultivated crop lands and killed over 460,000 head of livestock and poultry. In the past, the government of Bangladesh and development partners have provided substantial support to farmers in the aftermath of large disasters, but this approach has disadvantages in that support is not guaranteed to farmers and may be slow. In the aftermath of Cyclone Sidr, recovery and reconstruction needs were estimated at USD 1.3 billion, or 28 percent of government expenditures. In spite of efforts by the government of Bangladesh, the gap between available funding and needs is often large and can reach more than USD 1.5 billion in bad years (Air Worldwide and ADPC 2014). Bangladesh often relies on international assistance, as over the past ten years, only 33 percent of disaster-related expenses has been met by domestic resources. In addition, disaster relief transfers often take substantial time to reach beneficiaries and require to divert resources away from long term development projects. If the Government of Bangladesh decided to go ahead with support for agriculture insurance, high-level buy-in from a broad range of stakeholders will be necessary, as will partnerships with the private sector. Government may consider: strengthening the overall legal, regulatory, and supervisory insurance environment; developing a centralized database of data for agricultural insurance purposes; provision of financial support to the program, particularly in the early stages of the program; and establishing a dedicated technical team within government with responsibility for implementation and for providing input to policy. One option for consideration would be for some or all of these activities to be carried out through a project with technical support and/or financial assistance of a development partner with adequate expertise in this field, such as the World Bank Group.